2017
DOI: 10.1590/1413-81232017222.19952015
|View full text |Cite
|
Sign up to set email alerts
|

Insegurança alimentar no Brasil segundo diferentes cenários sociodemográficos

Abstract: Insegurança alimentar no Brasil segundo diferentes cenários sociodemográficosFood insecurity in Brazil in accordance with different socio-demographic scenarios

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
1
60

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 41 publications
7
34
1
60
Order By: Relevance
“…Saúde Pública 2019; 35 (7):e00084118 times more likely to be food insecure than those living with more than one minimum wage. The association between food security and income is well documented 5,20,21,24,34 and for this reason, Brazil has implemented several food security policies aimed to improve food access by the poor. For example: the Bolsa Família, which is considered the largest conditional cash transfer program in the world and covered a quarter of the Brazilian population in 2012; the Food Acquisition Program (PAA) that improves the income of smallholder farmers; and the Popular Restaurants that provide safe and nutritious meal at an affordable price (usually less than USD 1) 9,10,11 .…”
Section: Or 95%cimentioning
confidence: 99%
See 2 more Smart Citations
“…Saúde Pública 2019; 35 (7):e00084118 times more likely to be food insecure than those living with more than one minimum wage. The association between food security and income is well documented 5,20,21,24,34 and for this reason, Brazil has implemented several food security policies aimed to improve food access by the poor. For example: the Bolsa Família, which is considered the largest conditional cash transfer program in the world and covered a quarter of the Brazilian population in 2012; the Food Acquisition Program (PAA) that improves the income of smallholder farmers; and the Popular Restaurants that provide safe and nutritious meal at an affordable price (usually less than USD 1) 9,10,11 .…”
Section: Or 95%cimentioning
confidence: 99%
“…Many studies also showed that people with low levels of education have a higher risk of being food insecure, which is explained by its association with income 5,41 . Large family size, which is more common among the poor and low educated, was shown to be associated with food insecurity 5,18,22 . In our study, the risk of being food insecure did not differ among households with 1 to 5 residents but households with more than five residents were 35% more likely to be food insecure.…”
Section: Or 95%cimentioning
confidence: 99%
See 1 more Smart Citation
“…Considering income as a determinant of FI, bigger families need more resources to buy food, and income growth does not usually follow family growth [8], so a higher density of residents is an indicator of FI.…”
Section: Discussionmentioning
confidence: 99%
“…Food and Nutrition Insecurity is recognized as a complex and multidimensional phenomenon of multicausal determination [8]. Knowing the determinants of FI in a population or community allows researchers to deduce about its causes and proposing actions.…”
Section: Introductionmentioning
confidence: 99%